Identification of Best Practices of Higher Education Leadership in Shaping Student Character following Islamic Guidance - Rini Fitria; Abdul Rosid; Suwarni; Amirul Syah; Musyarrafah Sulaiman Kurdi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The study aimed to highlight best practices that showcased effective higher education leadership in character development at the university, substantiating these practices with compelling evidence rooted in Islamic principles. In pursuing this objective, a mixed-method approach was employed in the past. Qualitative data was collected through interviews and document analysis, while surveys and questionnaires provided quantitative insights. The study also reviewed relevant literature to contextualize Fatmawati University's character development efforts. The findings from this past study were illuminating. Fatmawati University effectively integrated Islamic ethics and morality into its academic curriculum through courses like "Islamic Ethics and Morality" and "Islamic Principles of Justice." The academic community actively engaged in charitable initiatives, reinforcing compassion and ethical conduct. Inclusivity was promoted through interfaith dialogues and cultural exchange events, fostering tolerance and understanding among students. Additionally, service learning, ethical discussions, and mentorship programs emphasized character development. The university's interdisciplinary approach, integrating Islamic studies across various academic disciplines, facilitated a holistic understanding of character development within Islamic ethics. In summary, Fatmawati University's past best practices in higher education leadership for character development underscored its commitment to Islamic principles, enriching students' character while promoting academic excellence and moral values. Keywords:  Islamic Ethics, Character Development, Education Leadership